Interdisciplinary Approach to the Analysis of the Dynamics of Legal Consciousness - I. L. Vershok (Сибирское юридическое обозрение, 2020)
The article deals with the dynamic aspects of legal consciousness. It is concluded that the traditional definition of legal consciousness as a set of emotions, ideas and feelings about the current and previously valid law was formed on the basis of the dominant materialistic concept as the ideological basis of knowledge in jurisprudence. Its use as a universal method determined the study of certain aspects of legal consciousness as an object of research activity, existing in the form of a reflection of the surrounding (legal) reality. As a result, the definition of legal consciousness in statics was formed, due to the analysis of individual external (materialized) signs of its manifestation (exteriorization). The existing lack of data on the peculiarities of the internal processes of the dynamics of legal consciousness was compelled to compensate for the study of mental processes and their corresponding parameters only on the basis of introspection. The article clearly demonstrates that this approach leads to various kinds of distortions, entailing errors in solving the fundamental problems of defining the phenomenon of legal consciousness, as well as a decrease in the quality of the practice of lawmaking and law enforcement. In order to overcome the gap that has arisen in theoretical and applied research, it is proposed to consider legal consciousness as a subject of scientific knowledge by constructing an integral theoretical scheme of its dynamics (flow) as a complex socio-psychological process. For this, an interdisciplinary approach is applied to the study of the dynamics of legal consciousness, on the basis of which a number of practical data from psychology, sociology, and cybernetics are synthesized. The definition of legal consciousness is formed on the basis of the decomposition of the concept into separate stages of legal consciousness with an analysis of their functional parameters. The main stages of the course of legal consciousness are recognized as the perception of the subject of legal regulation and its mediating legal norms with the formation of separate perceptual images, then – the corresponding perceptual activity with a certain centralization and cognitive processes with a possible result in the form of constructing mental schemes. The key parameters of legal consciousness are the generic-specific connection with consciousness, the absence of discreteness, as well as the specific formally-legally determined intentional orientation, temporality, coherence and tension of legal consciousness due to the subject's readaptation. Moreover, the target orientation, coherence and tension are largely predetermined by the methods and content of legal impact. As examples illustrating the proposed scheme of dynamics of legal consciousness, the phenomena of the so-called deformation of legal consciousness, approaches to the definition of subjectivity and legal personality, structural and substantive aspects of legal capacity and legal capacity, parameters of the subjective side of the offense, problems of professional legal consciousness and a number of other applied issues.